2002
DOI: 10.1021/jp020231n
|View full text |Cite
|
Sign up to set email alerts
|

Electron Dynamics in Nanocrystalline ZnO and TiO2 Films Probed by Potential Step Chronoamperometry and Transient Absorption Spectroscopy

Abstract: Potential step chronoamperometry is employed to compare the capacitances of nanocrystalline ZnO and TiO 2 electrodes. These capacitance data are complemented by transient optical absorption studies of charge recombination following adsorption of molecular sensitizer dyes to these metal oxide electrodes. Both measurements are conducted as a function of electrochemical bias applied to the metal oxide film in a threeelectrode photoelectrochemical cell. For both metal oxides, a power law dependence was observed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
155
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 42 publications
(97 reference statements)
14
155
0
Order By: Relevance
“…Examples are metal oxides used in DSC such as TiO 2 , ZnO and SnO 2 . [11][12][13][14][15] Colloidal nanocrystals are usually deposited over a conducting substrate and thermally treated to form a connected array of nanoparticles that can be used as electroactive electrodes. Structures can be more or less ordered, and interparticle connection can also be controlled with molecular ligands, which can be used to promote the self-assembly of special architectures.…”
Section: Nanoparticles and Nanostructuresmentioning
confidence: 99%
“…Examples are metal oxides used in DSC such as TiO 2 , ZnO and SnO 2 . [11][12][13][14][15] Colloidal nanocrystals are usually deposited over a conducting substrate and thermally treated to form a connected array of nanoparticles that can be used as electroactive electrodes. Structures can be more or less ordered, and interparticle connection can also be controlled with molecular ligands, which can be used to promote the self-assembly of special architectures.…”
Section: Nanoparticles and Nanostructuresmentioning
confidence: 99%
“…The corresponding density of states decay roughly exponentially below the band edge with an decay constant of a ) 15 (eV) -1 , similar to those used to model defect state densities of TiO 2 nanocrystalline electrodes in other studies. 31,32,77,78 This equation predicts that injection rate depends sensitively on the electronic coupling strength, the density of states per unit volume in the solid, and the relative position of adsorbate potential and band edge. Shown in Figure 10 are the calculated injection rate, k ET as a function of E CB -E(S + /S*).…”
Section: Ph Dependence Of Photophysicsmentioning
confidence: 99%
“…Such studies have been largely based by spectroelectrochemical studies of the density of conduction band/trapped electrons induced by electrical bias, 17 complimented more recently by a range of electrochemical techniques. [17][18][19][20][21] These studies have generally concluded that such films exhibit an exponential tail of states below the conduction band, attributed variously to defect states such as oxygen vacancies, surface states, and/or states induced by proton or lithium cation surface binding or intercalation into the TiO 2 nanoparticles. The energetics of this density of states has moreover been found to be strongly dependent upon the electrolyte composition, and in particular the concentration of small cations in this electrolyte.…”
Section: Introductionmentioning
confidence: 99%